Pathogenic LRRK2 negatively regulates microRNA-mediated translational repression. - Gehrke, S.; Imai, Y.; Sokol, N.; Lu, B. (Nature, 2010)
Gain-of-function mutations in leucine-rich repeat kinase 2 (LRRK2) cause familial as well as sporadic Parkinson's disease characterized by age-dependent degeneration of dopaminergic neurons. The molecular mechanism of LRRK2 action is not known. Here we show that LRRK2 interacts with the microRNA (miRNA) pathway to regulate protein synthesis. Drosophila e2f1 and dp messenger RNAs are translationally repressed by let-7 and miR-184*, respectively. Pathogenic LRRK2 antagonizes these miRNAs, leading to the overproduction of E2F1/DP, previously implicated in cell cycle and survival control and shown here to be critical for LRRK2 pathogenesis. Genetic deletion of let-7, antagomir-mediated blockage of let-7 and miR-184* action, transgenic expression of dp target protector, or replacement of endogenous dp with a dp transgene non-responsive to let-7 each had toxic effects similar to those of pathogenic LRRK2. Conversely, increasing the level of let-7 or miR-184* attenuated pathogenic LRRK2 effects. LRRK2 associated with Drosophila Argonaute-1 (dAgo1) or human Argonaute-2 (hAgo2) of the RNA-induced silencing complex (RISC). In aged fly brain, dAgo1 protein level was negatively regulated by LRRK2. Further, pathogenic LRRK2 promoted the association of phospho-4E-BP1 with hAgo2. Our results implicate deregulated synthesis of E2F1/DP caused by the miRNA pathway impairment as a key event in LRRK2 pathogenesis and suggest novel miRNA-based therapeutic strategies.